Keberkesanan Program Usahawan Muda (MYEP) untuk Meningkatkan Kemahiran Kontraktor dalam Projek Pembinaan MRT - Roslan, Aris Izuan; Omar, Roshartini; Mohamed, Sulzakimin; Masrom, Md Asrul Nasid (Research in Management of Technology and Business, 2021)
An effectiveness training program is a mechanism that drives an organisation towards excellence. However, various training programs take place during the waste. This situation stems from the courageous relationship of the training program and the training participants failing to transfer the acquired knowledge or skills to the workplace. This study aims to investigate the challenges faced in the MYEP skills training program, the effectiveness of the MRT Young Entrepreneur Program (MYEP) in increasing participants to become contractors in MRT development projects as well as measures to improve the work of bumiputera contractors who require MYEP training program. To achieve the objectives, an interview session was conducted between three (3) respondents who used the MYEP program. This research found that tmajority of the respondents agree on the challenges was moderately high, effectiveness and measures were high. Respondents claimed that background family, financial incentives and new skills are the biggest challenges to the effectiveness of the MYEP training program and the training program organizers and the government must take steps to increase training program participants in Malaysia. In conclusion, it is hoped that this study can benefit the organizers of training programs for guidance to determine the effectiveness of a program to be carried out.